2007
DOI: 10.1038/sj.cdd.4402188
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty2 inhibits BDNF-induced signaling and modulates neuronal differentiation and survival

Abstract: Sprouty (Spry) proteins are ligand-inducible inhibitors of receptor tyrosine kinases-dependent signaling pathways, which control various biological processes, including proliferation, differentiation and survival. Here, we investigated the regulation and the role of Spry2 in cells of the central nervous system (CNS). In primary cultures of immature neurons, the neurotrophic factor BDNF (brain-derived neurotrophic factor) regulates spry2 expression. We identified the transcription factors CREB and SP1 as import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 40 publications
3
62
0
Order By: Relevance
“…This has been observed by immunofluorescence analysis in brain sections as well as in dissociated cultures of cortical neurons. A similar staining pattern has been reported in primary cultures of cerebellar granule neurons (18), pointing to a not-yet-known nuclear role for Spry2.…”
Section: Discussionmentioning
confidence: 49%
“…This has been observed by immunofluorescence analysis in brain sections as well as in dissociated cultures of cortical neurons. A similar staining pattern has been reported in primary cultures of cerebellar granule neurons (18), pointing to a not-yet-known nuclear role for Spry2.…”
Section: Discussionmentioning
confidence: 49%
“…Despite all the data reported on Spry function, the molecular mechanisms by which Spry family members regulate branching are still unclear. In mammalian tissue culture systems, Spry proteins have been shown to inhibit Erk activation downstream of a plethora of growth factors, including FGF, VEGF-A, BDNF and GDNF (Cabrita and Christofori, 2008;Gross et al, 2007;Impagnatiello et al, 2001;Ishida et al, 2007;Taniguchi et al, 2009a). In Xenopus embryos, we have shown that Spry1 and Spry2 inhibit the Ca 2+ pathway downstream of FGF (Nutt et al, 2001;Sivak et al, 2005).…”
Section: Regulation Of Branching Morphogenesis By Spry Proteinsmentioning
confidence: 85%
“…Knockdown of Spry2 expression in murine embryonic lung cells in culture enhances branching morphogenesis (Tefft et al, 1999). In PC12 cells and cerebellar granule neurons (CGNs), overexpression of Spry2 reduces the number of neurites (Gross et al, 2007;Hanafusa et al, 2002;Sasaki et al, 2001). However, there is still a lack of evidence to support a role for Spry in axonal branching, as none of the knockouts reported to date shows a defect in the central nervous system.…”
Section: Introductionmentioning
confidence: 94%
“…Sprouty is a ligand-activated inhibitor that antagonizes receptor tyrosine kinase signaling in several contexts, such as Ras/ERK signaling in the developing compound eye (Kramer et al 1999;Hanafusa et al 2002). More notably, sprouty2-dependent signaling negatively regulates survival, differentiation, and growth in cultured immature neurons by antagonizing brain-derived neurotrophic factor (BDNF)-dependent signaling (Gross et al 2007). Precise analysis of this negative regulator in neural development and plasticity, however, has been lacking so far.…”
Section: Resultsmentioning
confidence: 99%